Collected essays on economic development - Chakraborty, Debashis (ed.) (New Delhi, 2008)
The current volume consists of seven articles contributed by eight Scottish Church College Department of Economics alumni, spanning over various spheres of economic development, namely: affirmative action in education, environmental sustainability, international trade, international credit market, infrastructure and economic history. Economic development is the common thread that binds all the articles in the volume together. The current volume is a tribute to Prof. Asok Barman of the Department of Economics, Scottish Church College by his students.
Keywords: Economic development